Basic Characteristics of Concrete Durability as the Criteria for Curing Classes Selection According to EN 13670:2009. (2015) - Łaskawiec, Katarzyna; Piotrowicz, Małgorzata; Romanowski, Piotr; Woyciechowski, Piotr
Abstract: In EN 13670:2009 standard: Execution of concrete structures there are general rules of moisture curing of concrete in structures. In the standard 4 classes of concrete curing are described. Determination of curing class depends on required level of compressive strength immediately after curing (percentage of required characteristic strength after 28 days). Time of curing depends on rate of strength development and concrete surface temperature. In the standard there is a lack of information about influence of curing class on concrete durability characteristics. The main condition to obtain durable concrete is proper curing regime. Not cured on improperly cured concrete has weakened surface layer. Extremely faults in curing process could lead to defects visible on the concrete surface. More often defects are latent inside the concrete and could be revealed during exploitation, leading to durability reduction. The main effect is increase of surface layer porosity (reinforcement cover) and decrease of its protective properties and tightness. Consequently worsening of mechanical properties could be observed as well as water-tightness, frost resistance, chemical aggression resistance, carbonation resistance and diffusivity of chloride. The analysis shown in the paper are the result of 3-yers long investigation conducted by authors, which main goal was to determine appropriateness and way to include durability requirements in designing of curing class according to EN 13670:2009. Thawing-freezing resistance, scaling with salts resistance, depth of water penetration under pressure and absorptivity were adopted as the basic durability factors. Concretes with different cement types, different rate of compressive strength development, air-entrained and non-air-entrained were tested. Time of curing was differentiated in the range of classes 1, 3, 4 following standard EN 13670:2009 requirements. Practical conclusions were formulated which allows to consider durability presumptions in technological requirements contained in concrete works specifications.